The Influence of Financial Anxiety, Financial Literacy, and Financial Digitalization on the Financial Stability of MSMEs in Mataram City - Lalu Fahril Dwi Suryadi; Burhanudin (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The financial stability of MSMEs in Mataram City is threatened by financial anxiety, low financial literacy, and suboptimal digitalization, with MSMEs dominating 10,471 micro-business units vulnerable to economic fluctuations. This study aims to examine the effect of financial anxiety, financial literacy, and financial digitalization on the financial stability of MSME actors. Using a causal quantitative design with PLS-SEM, the population of all MSMEs in Mataram (10,471 units), a sample of 120 purposive respondents, a 5-point Likert questionnaire instrument, and SmartPLS 4.0 analysis. The results show that financial literacy has a significant positive effect (coefficient 0.642, p = 0.000), financial anxiety has a significant positive effect (0.157, p = 0.030), while digitalization is insignificant (0.057, p = 0.461), with an R-square of 0.598. The conclusion recommends financial literacy training for the Cooperative Office to increase MSME resilience.